Penerapan Sentence BERT Untuk Similaritas Kompetensi Pekerjaan dan Mata Kuliah - Agiharta, Kafka Febianto; Suteja, Bernard Renaldy; Ayub, Mewati (Jurnal Teknik Informatika dan Sistem Informasi, 2024)
This research focuses on the application of the Sentence BERT (S-BERT) model, a specialization of the BERT model and an adaptation of the Transformer architecture specifically designed for the Indonesian language, in exploring the concept of course credit transfer consolidation in accordance with the Merdeka Belajar – Kampus Merdeka program. The aim of this exploration is to develop an Indonesian-language S-BERT model and apply it to search and analyze the similarity between activity sequence descriptions and course syllabus (RPS) descriptions. The results of this similarity analysis are the identification of relevant courses based on the given query. The developed model has shown effective capabilities in searching and determining the similarity between activity sequence descriptions and course syllabus descriptions. Courses identified as relevant to the query demonstrate high similarity and compatibility, indicating that the S-BERT model can be relied upon in the process of course credit transfer consolidation within the context of Merdeka Belajar – Kampus Merdeka.